Overexposure of a luxury brand : Coach Inc.'s distribution and image problem - Wilson, Matthew; Robson, Karen, (Assistant professor) (London : SAGE Publications: SAGE Business Cases Originals, 2019)
Coach Inc. is a luxury fashion brand, primarily known for its women's handbags. Through the 2000s and early 2010s, the brand pursued a strategy of expansion, leading to its merchandise being available in many locations--particularly in department stores. In 2014, the brand announced plans to reduce its distribution, citing concerns related to department store discounting of its merchandise and a related drop in brand status. In addition to cutting back on distribution, the brand renovated its own retail outlets, made changes to its products, and entered into a partnership with popular singer Selena Gomez. In response, sales of handbags in the price bracket of USD 400 or higher were up, as was perception of the Coach brand itself. This case provides an opportunity for students to explore the relationship between distribution and brand management, as well as to evaluate the steps Coach Inc. has taken to reposition itself as a luxury brand.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Coach Inc; Luxury goods industry -- Case studies; Fashion merchandising -- Case studies; Brand name products -- Management -- Case studies; Branding (Marketing) -- Case studies